Competition and persistence of R&D - Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2011)
This paper investigates the R&D persistence of R&D active firms in different markets with different intensities of competition, based on firm-level panel data for the period 1996-2008. In a dynamic setting of the empirical model it turns out that persistence is strongly related to market competition (measured by the number of principal competitors). Persistence of R&D expenditures is more likely to be observed in markets with few principal competitors (between 6 and 10) and is very unlikely to be observed in polypolistic type of markets (more than 50 competitors). These results call for a stronger coordination between competition policy and innovation promotion policy, since the former basically aims at larger markets with many competitors, while the latter aims at persistence of R&D efforts and thus markets with fewer competitors.
Keywords: O30; 330; R&D expenditures; Persistence; Innovation; Competition; Panel data; Empirical investigation; Industrielle Forschung; Dauer; Internationaler Wettbewerb; Innovationspolitik; Schweiz